Textdidaktische Gattungen: Etüden im Schreibunterricht? - Rezat, Sara (Feilke revisited. 60 Stellenbesuche)

Operatoren „to go”. Prozedurenorientierter Schreibunterricht. Basisartikel - Rezat, Sara; Feilke, Helmuth (Praxis Deutsch 274)

CLIL(iG) im Literaturunterricht der Sekundarstufe I? Konzepte der Fremdsprachendidaktik in einem integrativen Deutschunterricht am Beispiel von Emine Sevgi Özdamars „Karagöz in Alamania. Schwarzauge in Deutschland“ - Zierau, Cornelia; Kofer, Martina (Jahrbuch Deutsch als Fremdsprache 2016)

Stifterverband für die Deutsche Wissenschaft e.V.: Lehrkräftebildung für die Schule der Vielfalt. Eine Handreichung des Netzwerks Stark durch Diversität. (Mitautorin) - Zierau, Cornelia

Türkisch-deutsche Studien Jahrbuch 2018: Übersetzung als Kulturaustausch

Die Wissenschaftler und das verantwortliche Handeln im schweizerischen Drama. Friedrich Dürrenmatts Physiker Möbius und Lukas Bärfuss' Mediziner Gustav Strom - Famula, Marta (Vom Gipfel der Alpen... Das schweizerische Drama und Theater im 20. und 21. Jahrhundert)

„…ein gewisses Verhältnis zum Leben“. Die lebensweltliche Bedeutung der Schinkensemmel im Erzählwerk Thomas Manns - Famula, Marta (Dinge im Werk Thomas Manns (= inter/media 11))

Mechanical joining without auxiliary element by cold formed pins for multi-material-systems - Kraus, M.; Frey, P.; Kleffel, T.; Drummer, D.; Merklein, M. (AIP Conference Proceedings)

Vollvalidiertes thermisches Netzwerk eines RWDR- Ersatzsystems - Burkhart, C; Heimes, J; Weyrich, D; Magyar, Balázs; Sauer, B

Downturns are a better time for deal hunting - Kengelbach, Jens; Keienburg, Georg; Gell, Jeff; Nielsen, Jesper; Bader, Maximilian; Degen, Dominik; Sievers, Sönke (The 2019 M&A-Report)

Determinants of Financial Misreporting: A Survey of the Financial Restatement Literature - Sievers, Sönke; Sofilkanitsch, Christian

Oblique evanescent excitation of a dielectric strip: A model resonator with an open optical cavity of unlimited Q - Hammer, Manfred; Ebers, Lena; Förstner, Jens (Optics Express)
A rectangular dielectric strip at some distance above an optical slab waveguide is being considered, for evanescent excitation of the strip through the semi-guided waves supported by the slab, at specific oblique angles. The 2.5-D configuration shows resonant transmission properties with respect to variations of the angle of incidence, or of the excitation frequency, respectively. The strength of the interaction can be controlled by the gap between strip and slab. For increasing distance, our simulations predict resonant states with unit extremal reflectance of an angular or spectral width that tends to zero, i.e. resonances with a Q-factor that tends to infinity, while the resonance position approaches the level of the guided mode of the strip. This exceptionally simple system realizes what might be termed a “bound state coupled to the continuum”.
Keywords: tet_topic_waveguides

Sonderpädagogik als Erfahrungs- und Praxiswissenschaft. Geistes-, sozial- und kulturwissenschaftliche Perspektive - Dederich, M; Ellinger, S.; Laubenstein, Désirée

Beurteilung der Leistungsfähigkeit von Schmierstoffen mittels eines FZG Prüfstandes - Keßler, A; Elkenkamp, P; Magyar, Balázs; Mayer, C (Tribologie und Schmierungstechnik)

Teamentwicklung und Teamkooperation - Guthöhrlein, K.; Laubenstein, Désirée; Lindmeier, C.

Reibenergie basierte Verschleißsimulation für Radialwellendichtringe - Foko Foko, F; Sauer, B; Magyar, Balázs

The ‘Learning Office’ as an Approach for Inclusive Education in Mathematics: Opportunities and Challenges - Laubenstein, Désirée; Guthöhrlein, Kirsten; Lindmeier, Christian; Scheer, David; Sponholz, Dirk (In: Kollosche, D.; Marcone, R.; Knigge, M.; Godoy Penteado, M.; Skovsmose, O. (Hrsg.). Inclusive Mathematics Education. State-of-the-Art Research from Brazil and Germany)

Das Praxissemester von angehenden Lehrkräften - Caruso, Carina

Praxissemester (Religion) in NRW: Bilanz und Perspektiven - Caruso, Carina; Woppowa, Jan
Since the winter semester 2014 / 2015 long-term internships have become an integral part of the second master semester at universities in North Rhine-Westphalia. One aim is to improve the development of competencies of prospective teachers. This anthology provides an insight into perspectives of long-term internships in North Rhine-Westphalia referring especially to internships of those prospective teachers, who are going to be teachers for religious education. First Bardo Herzig and Christoph Wiethoff present the plan, the structure and the content of long-term internship at Paderborn University. They take pedagogy as their example. Petra Herzmann and Anke B. Liegmann provide a comprehensive survey of qualitative research on long-term internships and present ideas of a qualitative research programme. Carina Caruso and Andreas Seifert focus on the development of pedagogical knowledge of prospective teachers of religious education during the practice phase. Malte Kling gives a summary of his thesis referring to the change of roles of prospective teachers of religious education. Guido Hunze und Gudrun Lohkemper have a look at the relation between theory and practice for a successful professionalization. Norbert Brieden and Monika Tautz compare the accompaniment of students at Cologne and Wuppertal University and put forward an impetus for teaching at university. Mirjam Zimmermann looks at spirituality in internships. Guido Meyer and Carsten Misera give a definition of heterogeneity as a starting point of the development of the teacher habitus. Christoph Vogelsang and Ulrich Feeser-Lichterfeld contribute to a further combination of perspectives on internships. Carina Caruso and Jan Woppowa give a final summary looking especially at future tasks of the design of long-term internships in theology.

On the nomological net of (non-) workaholic subtypes - Ontrup, Greta; Patrzek, Justine (Career Development International)

Estimation of Nematic Order Parameters via Haller Analysis of 1H NMR Spectra of Liquid Crystals - Tang, Ming-xue; Schmidt, Claudia (Chinese Journal of Magnetic Resonance)
The Haller relationship was applied to estimate the nematic order parameter S from 1H NMR spectra of fully protonated liquid crystals aligned in the magnetic field. The NMR line shapes were approximated as doublets of very broad peaks. Both the temperature-dependent doublet Splitting and the full width at half maximum of the whole spectra were used for Haller extrapolation. The order parameters obtained with the proposed approach for 4-cyano-4'-pentylbiphenyl (5CB) and the nematic mixture E7 were found to be in good agreement with previously reports.
Keywords: nematic liquid crystal; order parameter; Haller analysis; 1H NMR

Speech Processing for Digital Home Assistance: Combining Signal Processing With Deep-Learning Techniques - Haeb-Umbach, Reinhold; Watanabe, Shinji; Nakatani, Tomohiro; Bacchiani, Michiel; Hoffmeister, Bjoern; Seltzer, Michael L.; Zen, Heiga; Souden, Mehrez (IEEE Signal Processing Magazine)
Once a popular theme of futuristic science fiction or far-fetched technology forecasts, digital home assistants with a spoken language interface have become a ubiquitous commodity today. This success has been made possible by major advancements in signal processing and machine learning for so-called far-field speech recognition, where the commands are spoken at a distance from the sound capturing device. The challenges encountered are quite unique and different from many other use cases of automatic speech recognition. The purpose of this tutorial article is to describe, in a way amenable to the non-specialist, the key speech processing algorithms that enable reliable fully hands-free speech interaction with digital home assistants. These technologies include multi-channel acoustic echo cancellation, microphone array processing and dereverberation techniques for signal enhancement, reliable wake-up word and end-of-interaction detection, high-quality speech synthesis, as well as sophisticated statistical models for speech and language, learned from large amounts of heterogeneous training data. In all these fields, deep learning has occupied a critical role.

„Die Schulbänke standen hintereinander“. Darstellendes Schreiben über die Schule früher - Tophinke, Doris (Praxis Deutsch)

Konstruktionale Aspekte schriftkultureller Autozentrierung im Spätmittelalter. Zu einer markanten Neuerung in der Buchführung der Hansekaufleute des 14. Jahrhunderts - Tophinke, Doris (Linguistische Kulturanalyse)

Muster - Tophinke, Doris (Feilke revisited. 60 Stellenbesuche)

Dialekte heute (Basisartikel) - Tophinke, Doris (Paxis Deutsch)

PSΦ: Forschungsprogramm zur Studieneingangsphase im Physikstudium - Bauer, Anna; Lahme, Simon; Woitkowski, David; Vogelsang, Christoph; Reinhold, Peter (PhyDid B – Didaktik der Physik – Beiträge zur DPG-Frühjahrstagung)

Vorerfahrungen, Einstellungen und motivationale Orientierungen als mögliche Einflussfaktoren auf den Einsatz digitaler Werkzeuge im naturwissenschaftlichen Unterricht - Vogelsang, Christoph; Finger, Alexander; Laumann, Daniel; Thyssen, Christoph (Zeitschrift für Didaktik der Naturwissenschaften)

Entwicklung von Professionswissen und Unterrichtsperformanz im Lehramtsstudium Physik. Analysen zu valider Testwertinterpretation - Vogelsang, Christoph; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Kulgemeyer, Christoph; Reinhold, Peter; Riese, Josef; Schecker, Horst; Schröder, Jan (Zeitschrift für Pädagogik)
Angehende Physiklehrkräfte sollen im Rahmen ihres Studiums fachliches und fachdidaktisches Wissen erwerben, welches die Gestaltung lernförderlichen Unterrichts ermöglicht. Es ist allerdings empirisch nur wenig geklärt, wie sich dieses Wissen im Laufe des Studiums entwickelt und ob es zur Ausbildung von Handlungsfähigkeiten beiträgt. Um derartige Wirkungsaussagen treffen zu können, müssen Instrumente entwickelt werden, die eine valide Testwertinterpretation zulassen. In diesem Beitrag werden auf Basis von im Projekt Profile-P+ entwickelten Instrumenten Validitätsanalysen zur längsschnittlichen Entwicklung des Professionswissens von Physiklehramtsstudierenden im Verlauf des Bachelorstudiums und ihrer Fähigkeiten zur Planung und Reflexion von Physikunterricht sowie zum Erklären von physikalischen Sachverhalten vor und nach dem Praxissemester dargestellt. Neben Wissenstests kamen standardisierte Performanztests zum Einsatz. Die vorliegenden Ergebnisse sprechen dafür, dass die erhobenen Messwerte im Sinne von Wirkungsaussagen interpretiert werden können. (DIPF/Orig.)

Encrypted Model Predictive Control in the Cloud - Schulze Darup, Moritz (Privacy in Dynamical Systems)

Towards real-time ADMM for linear MPC - Schulze Darup, Moritz; Book, Gerrit; Giselsson, Pontus (2019 18th European Control Conference (ECC))

Verschlüsselte Regelung in der Cloud – Stand der Technik und offene Probleme - Schulze Darup, Moritz (at - Automatisierungstechnik)
Zusammenfassung Zukünftige Regelungskonzepte werden verstärkt auf Cloud-Computing und verteiltes Rechnen setzen. In den resultierenden vernetzten Regelungssystemen werden sensible Daten über öffentliche Netzwerke kommuniziert und auf Plattformen Dritter verarbeitet. Verschlüsselte Regelungen zielen darauf ab, die Vertraulichkeit dieser Daten im gesamten Regelkreis zu sichern. Um dieses Ziel zu erreichen, werden klassische Regelungsalgorithmen so modifiziert, dass sie verschlüsselte Regeleingriffe basierend auf verschlüsselten Systemzuständen berechnen. Zum Einsatz kommen dabei homomorphe Verschlüsselungsverfahren, die einfache mathematische Operationen auf verschlüsselten Daten ermöglichen. Der Artikel erläutert die Implementierung verschlüsselter Regelungen anhand von drei wegweisenden Realisierungen in der Cloud.
Keywords: Electrical and Electronic Engineering; Computer Science Applications; Control and Systems Engineering

Efficient computation of RPI sets for tube-based robust MPC - Schulze Darup, Moritz; Teichrib, Dieter (2019 18th European Control Conference (ECC))

Deep reinforcement learning for wireless sensor scheduling in cyber–physical systems - Leong, Alex S.; Ramaswamy, Arunselvan; Quevedo, Daniel E.; Karl, Holger; Shi, Ling (Automatica)
Keywords: Electrical and Electronic Engineering; Control and Systems Engineering

Defensive deception against reactive jamming attacks in remote state estimation - Ding, Kemi; Ren, Xiaoqiang; Quevedo, Daniel E.; Dey, Subhrakanti; Shi, Ling (Automatica)
Keywords: Electrical and Electronic Engineering; Control and Systems Engineering

Interaktive Analyse historischen Grammatikwandels. Konstruktionsgrammatik trifft auf machine learning - Merten, Marie-Luis; Tophinke, Doris (Jahrbuch für Germanistische Sprachgeschichte)

Professionalisierung durch Portfolioarbeit – Ein Beitrag zur Erfassung der Reflexionskompetenz von Lehramtsstudierenden. - Stender, Jana; Schaper, Niclas; Vogelsang, Christoph; Watson, Christina (Lehrerbildung auf dem Prüfstand)

„All City“ – Graffiti-Writings als Kommunikate des Urbanen - Tophinke, Doris (Zeitschrift für Germanistische Linguistik)

Differentiability of the evolution map and Mackey continuity - Hanusch, Maximilian (Forum Mathematicum)
Keywords: regularity of Lie groups; differentiability of the evolution map

Über Mess-Manien und den Umgang mit zerteilten Informationen. - Laubenstein, Désirée (In: Dederich, M., Ellinger, S. & Laubenstein, D. (Hrsg). Sonderpädagogik als Erfahrungs- und Praxiswissenschaft. Geistes-, sozial- und kulturwissenschaftliche Perspektive.)

Performance-Oriented Testing and Training in Teacher Education - Vogelsang, Christoph; Borowski, Andreas; Kulgemeyer, Christoph; Riese, Josef; Reinhold, Peter; Schecker, Horst; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Schröder, Jan

Reflexionskompetenz trainieren: Unterrichtsvideographie als Werkzeug zur fachdidaktischen Begleitung im Praxissemester - Vogelsang, Christoph (Praxissemester (Religion) in NRW: Bilanz und Perspektiven)

Updatable Anonymous Credentials and Applications to Incentive Systems - Blömer, Johannes; Bobolz, Jan; Diemert, Denis Pascal; Eidens, Fabian (Proceedings of the 2019 ACM SIGSAC Conference on Computer and Communications Security - CCS '19)
In this paper, we introduce updatable anonymous credential systems (UACS) and use them to construct a new privacy-preserving incentive system. In a UACS, a user holding a credential certifying some attributes can interact with the corresponding issuer to update his attributes. During this, the issuer knows which update function is run, but does not learn the user's previous attributes. Hence the update process preserves anonymity of the user. One example for a class of update functions are additive updates of integer attributes, where the issuer increments an unknown integer attribute value v by some known value k. This kind of update is motivated by an application of UACS to incentive systems. Users in an incentive system can anonymously accumulate points, e.g. in a shop at checkout, and spend them later, e.g. for a discount.

Entwicklung und psychometrische Evaluation eines Fragebogens zur Erfassung subjektiver Definitionen von Inklusion. Posterpräsentation - Egener, Lea; Scheer, D.; Laubenstein, Désirée; Melzer, Conny

Scaffoldingelemente zur Sprachförderung im Textilunterricht. - Stenzel, Nadja; Drumm, Sandra (ProDaZ)

Das Praxissemester als Bildungsprozess - WoppowaC, Jan; Caruso, Carina (Praxissemester (Religion) in NRW: Bilanz und Perspektiven)

Studentisches Kompetenzerleben im Kontext schulpraktischer Anteile in der Religionslehrer*innenbildung - Caruso, Carina (Studium trifft Beruf. Praxisphasen und Praxisbezüge aus Sicht einer angewandten Theologie)

Integrated All Optical Sampling of Microwave Signals in Silicon Photonics - Misra, Arijit; Kress, Christian; Singh, Karanveer; Preussler, Stefan; Scheytt, Christoph; Schneider, Thomas (2019 International Topical Meeting on Microwave Photonics (MWP))
Optical sampling of pseudo random microwave signals with sinc-shaped Nyquist pulse sequences has been demonstrated in an integrated silicon photonics platform. An electronic-photonic, co-integrated depletion type silicon intensity modulator with high extinction ratio has been used to sample the microwave signal with a sampling rate, which corresponds to three times its RF bandwidth. Thus, a sampling rate of 21 GSa/s is achieved with a 7 GHz modulator, with 3 dBm of differential input power.

Integrated source-free all optical sampling with a sampling rate of up to three times the RF bandwidth of silicon photonic MZM - Misra, Arijit; Kress, Christian; Singh, Karanveer; Preussler, Stefan; Scheytt, Christoph; Schneider, Thomas (Opt. Express)
Source-free all optical sampling, based on the convolution of the signal spectrum with a frequency comb in an electronic-photonic, co-integrated silicon device will be presented for the first time, to the best of our knowledge. The method has the potential to achieve very high precision, requires only low power and can be fully tunable in the electrical domain. Sampling rates of three and four times the RF bandwidths of the photonics and electronics can be achieved. Thus, the presented method might lead to low-footprint, fully-integrated, precise, electrically tunable, photonic ADCs with very high-analog bandwidths for the digital infrastructure of tomorrow.

Midinfrared Birefringence of Liquid Crystals, Polarimetry, and Intensity Modulators - Atorf, Bernhard; Auf der Landwehr, Chris Holm; Rennerich, Roman; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry B)